1990
DOI: 10.1021/j100381a064
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and pressure dependence of hydrogen bonding in liquid methanol studied by nuclear magnetic resonance

Abstract: modeling of diffuse scattering; indeed, the analysis of local correlations in these strongly disordered crystals seems as important as the structure refinement. Then, it will hopefully be possible to think about microscopic models to interpret the distribution of proton tunnel splitting since that fascinating observation did in fact occasion the whole work.Acknowledgment. We thank José Dianoux and Werner Press for very useful discussions or comments on the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
25
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 5 publications
9
25
0
Order By: Relevance
“…For the HB fluids, a large number of studies performed by NMR and IR had shown that the number of hydrogen bonds is closely related to temperature and pressure [6][7][8][9][10][11] , so we predict that the volume change due to hydrogen bonds should be a function of T and P , too. Considering that the real system evolves into the state II( 2 2 2 , , P V T ) from the state I( 1 1 1 , , P V T ), as a generalization of the above discussions,…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…For the HB fluids, a large number of studies performed by NMR and IR had shown that the number of hydrogen bonds is closely related to temperature and pressure [6][7][8][9][10][11] , so we predict that the volume change due to hydrogen bonds should be a function of T and P , too. Considering that the real system evolves into the state II( 2 2 2 , , P V T ) from the state I( 1 1 1 , , P V T ), as a generalization of the above discussions,…”
mentioning
confidence: 84%
“…The existence of hydrogen bonds restricts the molecular motions, and leads to some effects on the properties of HB fluid systems. A large number of the studies had shown that for a HB fluid system, the changes in pressure and temperature can result in the change in the number of hydrogen bonds, and it is favorable for hydrogen bond's formation that lowers temperature and pressure [6][7][8][9][10][11] . Thus with temperature decreasing and pressure increasing, on the one hand, the volume of HB fluids will decrease as that in usual fluids; on the other hand, the HB process also contributes to the volume's decreasing, and the contribution is related to the number density of molecules and molecular structure.…”
mentioning
confidence: 99%
“…In low-temperature IR and Raman studies [27] of X-and Y-faujasites, SiO 4 ''rotational'' modes were observed near 100 cm À1 . However, aside from acoustic lattice modes, the only modes identified below 100 cm À1 were cation modes.…”
Section: C-x Stretching Mmentioning
confidence: 99%
“…The TBH loaded Na-X coalescence was, thus, treated as an exchange of a vibrational quantum between the guest vibrational mode and one host vibrational mode. NMR studies have been done on solution intermolecular proton exchange line coalescence between the chemical shifts of two different chemical species [27]. These phenomena were shown to obey a mole fraction-weighted law of chemical exchange [27].…”
Section: C-x Stretching Mmentioning
confidence: 99%
See 1 more Smart Citation